Hubungan Kepemimpinan dengan Kinerja Tenaga Kesehatan di Puskesmas Labuhan Ruku, Kec. Telawi, Kab. Batu-Bara - Amira, Annisa Puti; Nasution, Eka Madani; Nurhidayah, Nurhidayah; Rahma, Shinta; Mariani, Tia; Gurning, Fitriani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Leadership style is considered important because the success of an organization will be determined by the leadership style of a leader. Leadership style is a way that leaders can influence the work behavior of their employees. In addition to leadership style, there is also work motivation which is equally important to be examined because not many people realize that motivation plays a primary role in shaping behavior, as well as influencing performance in an organization. Both of these things must be possessed by a head of a community health center to develop the performance of healthcare workers working in the community health center. This study uses qualitative research methods, in which the approach method is through direct interviews at Labuhan Ruku Community Health Center, Telawi Subdistrict, Batu-Bara Regency. This study aims to determine how the relationship between the leader and healthcare workers in this community health center. The results obtained from this study are that the leader has a fairly harmonious relationship with healthcare workers. It is concluded that both the leader and healthcare workers as well as the staff at Labuhan Ruku Community Health Center, Telawi Subdistrict, Batu-Bara Regency have a very good relationship. This also affects the performance of healthcare workers and staff to do their jobs well and as best as possible.